Phenotypic and marker‐assisted pyramiding of genes for resistance to zucchini yellow mosaic virus in oilseed pumpkin (Cucurbita pepo). Issue 1 (1st December 2014) - Pachner, Martin; Paris, Harry S.; Winkler, Johanna; Lelley, Tamas; Debener, T.
Abstract We report on the identification of phenotypic and molecular markers for genes introgressed into oilseed pumpkin Cucurbita pepo from C. moschata germplasm originating in Nigeria, Portugal and Puerto Rico, which provide resistance against zucchini yellow mosaic virus (ZYMV) and on pyramiding these genes for improved and long‐lasting field protection of oilseed pumpkins. One SCAR and two SSR markers have been found for three dominant resistance genes, Zym‐0, Zym‐1 and Zym‐2. Characteristic reactions to ZYMV inoculation of plants carrying the recessive genes for resistance zym‐4* and zym‐6 have been defined. Described are procedures and results of pyramiding various combinations of these genes in oilseed pumpkin using the three markers and the specific phenotypic reactions to infection of some of these genes. The putative combination of all six resistance genes in one genotype resulted in a resistance that appeared to be at least as strong as or even stronger than that of the resistance source germplasm in C. moschata.